Clinical and radiological features of atlantoaxial dislocations associated with congenital malformations of the craniovertebral junction - Olga M. Pavlova; Sergey O. Ryabykh; Aleksandr V. Burtsev; Alexandr V. Gubin (Хирургия позвоночника, 2018)
Objective. To analyze clinical and radiological features of congenital atlantoaxial dislocations (AAD) in congenital craniovertebral junction malformations. Material and Methods. The data of 26 patients with AAD associated with congenital pathology of the craniovertebral junction, who applied to the Ilizarov Center in 2012–2017, were analyzed. Results. Patients were divided into three groups: with non-syndromic AAD – 6 (23.1 %) patients, with AAD associated with Klippel – Feil syndrome – 11 (42.3 %) and with syndromic AAD – 9 (34.6 %). Odontoid anomalies were observed in 15 (57.7 %) patients, the magnitude of dislocation was determined from the C1 facet displacement relative to that of C2 in different planes. Patients with non- syndromic AAD had local pain syndrome (VAS score 4.20 ± 2.64) accompanied by torticollis and restriction of head movements, and myelopathy. In patients with AAD associated with Klippel – Feil syndrome, the local symptoms prevailed: restriction of neck movements, torticollis, neck pain (VAS score 2.40 ± 2.01), and myelopathy. Myelopathy and unpronounced pain syndrome (VAS score 2.30 ± 1.94) were leading symptoms in patients with syndromic AAD. Conclusion. Patients with syndromic AAD more often have myelopathy, whereas AAD with the Klippel-Feil syndrome and non-syndromic AAD are often manifested by local symptoms.